Capacidad de la infusión de oxitocina para reducir la pérdida sanguínea durante la miomectomía abdominal - Sánchez Villalobos, Mónica Vanesa (2022)
Objective: Evaluate the effectiveness and security of oxytocin infusion por reduce blood loss during abdominal myomectomy. Methods: electronic research in Cochrane library, MEDLINE, EMBASE and LILACS between 2010 and 2021, for randomized controlled trials (RCT), where oxytocin against placebo was compared in abdominal myomectomy. Results: We found evidence of a significant difference between oxytocin against placebo regarding blood loss: Mean Difference (MD) -315,86 ml, IC del 95%: (−389,05 a 242,67), hemoglobin decrease (Hb g/dl): MD -0.60, IC del 95%: (−0.85 a 0.36), duration of surgery: MD -14,10 min; IC del 95%: (-19,3 a -8,32) and need for blood transfusion RR 0,28 IC del 95%:(0,13 a 0,58). Conclusion: It was demonstrated that oxytocin reduces perioperative blood loss, decrease in hemoglobin, surgical time and the need for blood transfusion subsequent to abdominal myomectomy.